Factors That Affect the High Incidence of Pulmonary Tuberculosis - Nurdiamsyah, Muh; Patiku, Yudit; Mashyuri, Robertus (Omni Health Journal, 2025)
Background: Indonesia ranks second globally in the burden of tuberculosis (TB), following India. The World Health Organization (WHO) estimates 969,000 TB cases in Indonesia, with 717,941 officially reported. In 2022, TB case detection increased significantly across health facilities, involving 97% of health centers, 85% of government hospitals, and over 80% of private hospitals, indicating the continued urgency of TB control efforts. Objective: This study aims to identify the contributing factors to the incidence of pulmonary tuberculosis in the working area of the Tamalatea Health Center, Jeneponto Regency. Methods: This research employed a descriptive design involving 30 respondents selected through purposive sampling. Data were collected using structured observation sheets and analyzed descriptively to identify the influence of socioeconomic, knowledge, and environmental sanitation factors on TB incidence. Results: The majority of respondents (96.7%) were classified as having low socioeconomic status. In terms of knowledge, 93.3% had good awareness of pulmonary TB, while 6.7% demonstrated low knowledge. Regarding environmental sanitation, 86.7% lived in homes with good conditions, while 13.3% lived in environments considered poor in sanitation. Conclusion: Low socioeconomic status appears to be the most dominant factor influencing the incidence of pulmonary tuberculosis in this area. It is recommended that local government strengthen the empowerment of both human and natural resources to improve community income and reduce TB vulnerability.